Karakteristik Sifat Fisik Tanah pada Lahan Budidaya Talas Beneng (Xanthosoma undipes K. Koch) Berdasarkan Perbedaan Ketinggian: Characteristics of the Physical Properties of Soil in Talas Beneng (Xanthosoma undipes K. Koch) Cultivation Areas Based on Altitudinal Differences - Sholihat, Aghnia; Hermita, Nuniek (Gontor Agrotech Science Journal, 2025)
. The physical characteristics of soil play an important role in determining land quality and environmental conditions. Physical properties such as texture, structure, and permeability are key indicators in assessing agricultural land quality. Therefore, analyzing soil physical properties at various elevations is essential to determine the most suitable locations for optimal Beneng taro cultivation. This study aims to examine the physical characteristics of soil in Beneng taro cultivation areas at different altitudes. A descriptive quantitative method was used in three locations with varying elevations: Talaga Warna Village in Pabuaran District (343 meters above sea level), Juhut Village in Karangtanjung District (615 meters above sea level), and Kaduengang Village in Cadasari District (761 meters above sea level). The tested soil physical parameters included texture, structure, and permeability. Soil samples were collected using a ring sampler at a depth of 0–20 cm and analyzed at the Soil Laboratory of Sultan Ageng Tirtayasa University and Laboratory of the Department of Soil Science and Land Resources, Faculty of Agriculture, IPB University. The results showed that the soil texture across all Beneng taro cultivation areas was predominantly sandy clay. The soil structure ranged from moderately to coarsely granular, while the soil permeability class was categorized as fast to moderately fast.